Financial Access and Stability : A Road Map for the Middle East and North Africa - Rocha, Roberto R. (World Bank, 2012)
This report contributes to the effort to improve Middle East and North Africa's (MENA's) growth and employment performance by providing a diagnostic of MENA's financial systems and proposing a roadmap for more diversified, competitive, and inclusive financial systems. The report recognizes the need to complement the financial development agenda by a financial stability agenda, to ensure that financial systems remain resilient as access is expanded and new risks emerge. The report starts by briefly reviewing the main causes of MENA's unsatisfactory growth and employment performance, identifying the region's broader growth agenda and the role of financial development in this agenda. It proceeds by reviewing the size and structure of MENA's financial systems, showing that most of these systems are excessively bank based and undiversified. The chapter provides a battery of access indicators showing that access outcomes have been very poor relative to those in other regions. It discusses the main causes of these poor outcomes and proposes a comprehensive agenda for financial development and financial stability. The report emphasizes the many common challenges faced by MENA countries, but it also recognizes the differences and tailors policy recommendations to the initial conditions in each of the main sub regions.